Keragaan Tanaman dan Kelayakan Finansial Teknologi Usahatani Padi Jajar Legowo Super di Kabupaten Karanganyar, Jawa Tengah - Chanifah, Chanifah; Kushartanti, Ekaningtyas; Praptana, Raden Heru; Khosiyah, Parti (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
Jarwo super technology is a combination of superior rice farming technology, including the 2:1 paired rows planting system, high yield potential varieties, bio-decomposers, biological fertilizers, bio-pesticides, and agricultural mechanization application. The assessment aims to determine plant diversity, production increase, and financial feasibility of jarwo super technology rice farming. The assessment was conducted on March-Juni 2017 with the â€œdemplotâ€ method of applied jarwo super technology in Karanganyar Regency, Center of Java. Primary data is growth, production, and rice farming performance at the â€œdemplotâ€, as well as existing farmer data. Samples were collected purposively, itâ€™s the farmers who carried out the â€œdemplotâ€ and the farmers around the â€œdemplotâ€, which meant 30 farmers. Data were descriptively analyzed using the average value, RCR, MBCR, net profit value, and BEP. The results showed that the rice yields with jarwo super was 15.63%higher than the existing farmers. Jarwo super rice farming is more efficient and economically feasible with RCR 1.44 value. MBCR is 11.6 value, it that each additional cost of implementing jarwo super rice farming of 1.000 IDR increases income by 11.600 IDR. Proportion of costs increase in jarwo super rice farming is 350.000 IDR, but profits reached 4.077.083 IDR. Net profit value of 1.7 shows that jarwo super rice farming can increase profits. Production level and dry grain harvested price on farmers level were 30.76%higher compared to BEP production and BEP price. Jarwo super rice farming is feasible to develop that because can increase farmerâ€™s production and profits.